Oor die betekenis van die maagdelike geboortetradisie: "n Debat in die Nederduitsch Hervormde Kerk - Boshoff, P. B. (HTS teologiese studies, 2004)
The meaning of the tradition of the virgin birth: A discussion in the Nederduitsch Hervormde KerkThis essay explains the meaning attached to the tradition of the virgin birth according to conservative, liberal and balanced readings. Topics that feature in the course of the argument are fundamentalism, liberalism, kerygma and the experience and verbalisation of the kerygma. Fundamentalism is defined as the inability to discern between gospel and theology. Liberalism is the willingness to renounce the concept of revelation. The gospel is proclaimed by performative language. Dogma is the explanation of belief which precedes it. In conclusion an explanation of the meaning of the tradition of the virgin birth based on proposed hermeneutical principles, is given.